Impact of fractures on quality of life in patients with osteoporosis: a US cross-sectional survey. (1st January 2019) - Gold, Deborah T.; Williams, Setareh A.; Weiss, Richard J.; Wang, Yamei; Watkins, Christopher; Carroll, James; Middleton, Chloe; Silverman, Stuart
Abstract: Objective: To evaluate the impact of osteoporosis-related fractures on health-related quality of life (HRQoL). Methods: Data were obtained from the 2016 Adelphi US Osteoporosis Disease Specific Programme™, a cross-sectional survey of physicians and their male and female patients with osteoporosis. Patient-reported outcomes (PRO) measures included the European Quality of Life 5 Domains (EQ-5D), European Quality of Life Visual Analog Scale (EQ-VAS), and Osteoporosis Assessment Questionnaire short-version (OPAQ-SV; physical, emotional, and symptom domains). Associations between PRO scores and the number and site of fractures were evaluated using ANOVA. Multivariate analyses were conducted using linear regression. Results: Physicians provided records for 1848 patients with osteoporosis. Of these, 981 (53.1%) completed the patient survey, data for the number of fractures were available for 935/981 (95.3%), and 185/935 (19.8%) had a history of fracture. Experiencing fractures significantly influenced scores on all PRO measures ( p < .0001). Hip and spine fractures were associated with the greatest reduction in most PRO scores. The number of fractures, age, body mass index, and Charlson Comorbidity Index (CCI) were significantly associated with PRO measures ( p < .05) in multivariate analyses. In patients with a fracture, fracture site, CCI, gender (EQ-5D and EQ-VAS), and age (OPAQ-SV physical only) were significantly associated with PRO measures. Conclusions: In patients with osteoporosis, fractures are associated with lower HRQoL and lower overall health status. Fracture history, fracture site, age, and comorbidity burden significantly influence HRQoL in individuals with osteoporosis. These data suggest the need for interventions to reduce the risk of fractures in patients with osteoporosis.